ANALISIS NILAI KARAKTER BUKU DONGENG TIMUN MAS KARYA ARYASATYA IKRANEGARA PADA SISWA KELAS III SD NEGERI WANASARI 01 - Rifqi Yatul Janah; A.Y. Soegeng Ysh; Joko Sulianto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The purpose of this study was to identify the character values contained in the fairy tale book Timun Mas by Aryasatya Ikranegara in third grade students of SD Negeri Wanasari 01. The type of research used was qualitative with descriptive method. Data collection techniques were carried out by means of observation, interviews, and documentation. Checking the validity of the data is done by means of technical triangulation. The method of analysis is data reduction, data presentation, and verification/conclusion. Based on the results of data analysis in this study, the fairy tale book Timun Mas by Aryasatya Ikranegara contains character values, including religious, honest, creative, independent, curious, communicative, hard working, peace loving, social care and responsibility. Character values that have not been listed in the fairy tale book Timun Mas by Aryasatya Ikrangara are tolerance, discipline, democracy, national spirit, love for the homeland, respect for achievements, love to read, and care for the environment. It is hoped that there will be improvements in the inclusion of character values in it, so that the book can be used as a reading reference material for planting character values to the fullest. Tujuan dari penelitian ini adalah untuk mengidentifikasi nilai karakter yang terdapat dalam buku dongeng Timun Mas karya Aryasatya Ikranegara pada siswa kelas III SD Negeri Wanasari 01. Jenis penelitian yang digunakan adalah kualitatif dengan metode deskriptif. Teknik pengumpulan data dilakukan dengan cara observasi, wawancara, dan dokumentasi. Pengecekan keabsahan data dilakukan dengan cara triangulasi teknik. Metode analisis dengan cara reduksi data, penyajian data, dan verifikasi/kesimpulan. Berdasarkan hasil analisis data dalam penelitian ini, maka dalam buku dongeng Timun Mas karya Aryasatya Ikranegara mengandung nilai karakter antara lain religius, jujur, kreatif, mandiri, rasa ingin tahu, komunikatif, bekerja keras, cinta damai, peduli sosial dan tanggung jawab. Nilai karakter yang belum tercantum dalam buku dongeng Timun Mas karya Aryasatya Ikrangara adalah toleran, disiplin, demokratis, semangat kebangsaan, cinta tanah air, menghargai prestasi, gemar membaca, dan peduli lingkungan. Diharapkan adanya perbaikan dalam pencantuman nilai karakter di dalamnya, agar buku tersebut dapat digunakan sebagai bahan referensi bacaan penanaman nilai karakter secara maksimal.